The Effect of Corruption and Inflation on Economic Growth in ASEAN - Marta Angelina Fenela Saragih; Darwin Damanik; Pawer Darasa Panjaitan (Budapest International Research and Critics University, 2022)
This study aims to determine the effect of corruption and inflation variables on economic growth in ASEAN for the period 2017-2021. The method used in this study is a quantitative method. The data used is secondary data obtained from World Data, Transparency International (TI), Central Statistics Agency (BPS) and Bank Indonesia (BI). And the research model used in this study is the panel data regression model. The results of the study using panel data regression with Common Fixed Effect stated the results of the Partial Test (t) that the Corruption Variable (X1) had a negative and insignificant effect on economic growth (Y). While the Inflation Variable (X2) inflation has a positive and insignificant effect on economic growth (Y). Simultaneous Test Results (F) state that corruption and inflation together have no significant effect on economic growth.